Reasons for selecting study program: Perspectives of English Language Education Study Program Students - Yunia, Khansa Qurota; Trisila, Feby Setya; Purwanti, Eko (Universitas Muhammadiyah Yogyakarta, 2025)
It is widely acknowledged that education is paramount for all members of society. However, there has been a notable decline in the number of individuals interested in pursuing a career in teaching. This results in many students opting to pursue their studies in other academic fields rather than continuing their education in the education department. Upon reflection, it becomes evident that the motivations underlying students' decisions to enroll in these programs do not align with the department's primary objective, which is to prepare individuals to become educators. This study aims to ascertain whether students aspire to become educators or merely wish to pursue studies in this field to gain proficiency in the language. A qualitative research approach was employed to address the research questions through interviews. In the interviews, the author inquired of five participants in the English education program at UMY. The findings of this study indicate that all five participants expressed a lack of interest in pursuing a career as a teacher. Upon completion of their studies, participants can use the language skills acquired at the institute to pursue alternative career paths. Based on their academic majors, this methodology allows for examining students' interest in pursuing teacher certification.